Finite element modelling of fixed-fixed end plate attached with vibration absorber - Mohamed Salleh, Muhammad; Zaman, Izzuddin (Asian Research Publishing Network (ARPN), 2016)
The present paper investigated the effect of the lightweight dynamic vibration absorber (LDVA) to reduce vibration of thin walled structure. The free and forced vibration response of a rectangular thin plate were performed using finite element method. Subsequently, the effects of attached single and dual LDVA were analysed in depth by using Ansys workbench 14.5. Results demonstrated that single LDVA attached at the centre of the plate succesfully attenuate vibration over the frequency range of 0- 600 Hz. By contrast, attached with dual LDVA only suppresses the resonance of the first second and fourth modes but not for third and fifth modes of thin walled structure. It was found that by simply increasing the weight of mass does not improve the vibration absorption over the entire frequency range. The study conclude that attached single LDVA are better than dual LDVA for vibration absorption of thin walled structure over the entire frequency range.